How might we use Design Thinking for Digital Business Design and for creating Digital Business Value? - Peter Baum (International Telecommunications Society (ITS), 2018)
Established organisations seek to reinvent or enhance their business models at a time when the rate of innovation accelerates and a transformation, such as the current digital transformation, drives the global economic environment. Design Thinking (DT) is a new methodology that has been hailed as a method to identify, understand and solve dynamic business issues. This paper investigates how the DT methodology supports an organization in finding new ways of creating, delivering, and capturing digital business value in dynamic environments. After determining the characteristics of business model creation in dynamic environments, we demonstrate how the Design Thinking methodology can guide an organisation through a digital transformative process to capture digital business value.
Keywords: 330